TO STUDY THE ADOPTION AND APPLICATION OF HR ANALYTICS AMONG HR PROFESSIONALS IN THE ORGANIZATIONS - Preeti Sharma (International Journal of Multidisciplinary Research and Studies, 2023)
Business facts and data supporting these goals are essential for corporate strategic plans. Data-driven decision-making, evidence-based initiatives, prioritizing the effects of HR investments, and improved company value and performance are all promised benefits of HR analytics. This study seeks to understand why Saudi HR professionals do not employ HR analytics to improve corporate performance and preserve a competitive edge. The descriptive survey research design is employed. The adoption of HR analytics by human resource professionals at the individual level is the main topic of this study. The study design is a descriptive survey. This paper's major goals are to comprehend the significance of HR analytics and to learn more about the obstacles that prevent HR professionals from fully implementing HR Analytics. The study's entire sample included 134 HR experts who worked for Manufacturing Firms in Haryana. The questionnaire that was distributed to the target sample via LinkedIn, WhatsApp, and the work's official email served as the main source of data for this study. The use of HR analytics and the other parameters are found to have beneficial links in the study.